CHRISTIANITY AND ISLAM IN THE CONTEXT OF CONTEMPORARY CULTURE: NEW PERSPECTIVES ON DIALOGUE AND MUTUAL UNDERSTANDING (Религиски дијалог и соработка, 2022)
This research is dedicated to the perspectives of dialogue betweentwomajorworld religions: Christianity and Islam in the context of contributing to the developmentof the contemporary world. Mutual respect and understanding expressedthroughinitiatives for constructive dialogue and cooperation can contribute to the consolidationof a culture of peace, to the promotion of social interaction and to the strengtheningofthe creative potential of society. The focus on the common heritage of both religious traditions, representedbythemultitude of insights and archetypes of Abrahamic origin, is the starting point for progressin the dialogue. Regarding this, the need arises to reform educational programs atalllevels in education by introducing more religious-ethical content that will conveythemessage of fruitful inter- religious dialogue between different social groups, inordertostrengthen and promote social cohesion and to create a common dimensionof culturaland spiritual progress.In the proper setting of the teaching process, students can feel that fully belongtothecompetence of action and change, no matter how beginner it may seemat theirage.Thus peace-pedagogical stimuli receive a new emphasis that extends to caringforthecreated world. Justice is understood as a decisive condition for peace and preservationofthe created world.